Financial Deepening in Sub-Saharan Africa : Empirical Evidence on the Role of Creditor Rights Protection and Information Sharing - McDonald, Calvin (IMF Working Papers; Working Paper ;, 2007)
This paper investigates the role of creditor rights and information sharing in explaining why some financial markets in sub-Saharan Africa have remained shallow. The paper finds that while financial liberalization and macroeconomic stability promote financial deepening, they are not enough. For countries with similar financial liberalization efforts, those with stronger legal institutions and information sharing have deeper financial development. This result is consistent with a growing body of research for other regions of the world. The main policy implications are that (1) creditor rights legislation should be reinforced, the law reformed, and efficient property registries established; and (2) governments should sponsor credit bureaus where private bureaus might not be commercially viable.